Impact of effective counselling on management of moderate acute malnutrition in a community - Arya, Vikas; Gaur, Ajay; Agarwal, Neetu S.; Chouhan, Harsha (International Journal of Contemporary Pediatrics, 2020)
Background: Moderate Acute Malnutrition (MAM) is defined as Weight for Height between -2SD to -3SD, and/or Mid Upper Arm Circumference (MUAC) 11.5 cm to 12.5 cm. Effect of not treating MAM has a significant impact on Severe Acute Malnutrition (SAM) burden. Management of MAM is possible through supplementary feeding or Community centre counselling. Methods: Present study was a prospective case control study done in 2013-14 in 200 children in adjacent communities. Community in which intervention (dietary counselling) was planned, it was labelled as case group. For dietary counselling ‘structured group counselling’ method was selected in which at a time parents of six MAM children were involved. Counselling was done by a trained counsellor using all techniques proposed by IYCF. Counselling sessions were scheduled at 0, 1, 3 and 6 months. Results: 60% children of case group moved to improved or well- nourished nutritional status (p-value 0.00001). Amongst improved group, weight for height improvement is statistically significant (p-value 0.001), average weight attained is 2-3 kg in 6 months with average weight gain of 1.5-3 grams/kg/day. MUAC improvement was also found to be statistically significant (p-value 0.003), there was 47% improvement in case group with average MUAC gain is 0.6 cm to 1 cm in 6 months (0.13 cm/month). Also, there is early rise in weight for height then MUAC. Average duration to achieve target weight for height is 4.3 months in case group as compare to 5.3 months in control group. Conclusions: Structured and integrated group counselling using all counselling skills by a trained counsellor should be an integral part of managing MAM in community. Weight for height should be primary indicator in early phase of response as compare to MUAC in measuring impact of counselling.